Geochemistry, origin and accumulation of continental condensate in the ultra-deep-buried Cretaceous sandstone reservoir, Kuqa Depression, Tarim Basin, China. (August 2015) - Zhu, Guangyou; Wang, Huitong; Weng, Na; Yang, Haijun; Zhang, Ke; Liao, Fengrong; Neng, Yuan
Abstract: A continental condensate field, with the deepest burial depth (7084 m) so far in China, was recently discovered from the Cretaceous sandstone reservoir in the Bozi area of the Kuqa Depression, Tarim Basin. In this paper, we report general features of this field, including geochemistry of the condensates, their origin, and migration and accumulation. General geochemistry of the condensate reflects that it is an over pressured condensate reservoir. Analytical results by newly-developed high-resolution GC × GC–TOFMS method indicate that the condensate is rich in n -alkanes from nC3 to nC34 and in diamondoid hydrocarbons with a high content of adamantanes. The condensate has a high abundance of aromatic hydrocarbons. The gas δ 13 C2 values in these are −23.3‰, which is characteristic of coal-derived gases. Compared with the contents of conventional condensate oils, the BZ1 well has a high content of aromatic hydrocarbons, suggesting that the condensate is in a stage of highly mature cracking. Analyses of oil biomarkers, carbon isotopes, gas compositions, etc., revealed that the condensate is dominantly sourced from the highly mature coals of the Jurassic Qiakemake Formation in the western Kuqa Depression. This set of coal source sequences has generated large quantities of condensate since 3 Ma, when the study area was subjected to a rapid subsidence with sediments over 2000 m and consequently attained at the condensate-generating stage. Such condensates then migrated vertically into the Cretaceous traps along faults. Therefore, the Bozi condensate field is a typical case of large-scale oil/gas field characterized by late-stage accumulation. Multiple elements favor the formation of this large-scale condensate field. The timing of trap formation accords with that of the condensate generation (since 3 Ma). The traps and source rocks are stacked vertically. Faults connect the source rock sequences and the reservoirs. The hydrocarbon charge is strong and efficient. Thick Paleogene gypsum beds act as an excellent cap rock, favoring the accumulation and preservation of the condensate. Highlights: Geochemistry, origin and accumulation of deepest-buried continental condensate in China. Condensate is rich in diamondoids with a high content of adamantanes and aromatic hydrocarbons. Condensate is in the stage of highly mature and cracking, and Jurassic coal-derived. Late-stage accumulation.